Nilai-Nilai Pendidikan Akhlak pada Film Sang Kiai terhadap Penanaman Akhlak dalam Dunia Pendidikan Islam Kontemporer - Rana Farras Irmi; Salminawati Salminawati; Zaini Dahlan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research aims to describe the positive impact of the development of television through film, especially in presenting deep moral values. The research method used is Library Research with a qualitative approach. Data was collected through written sources, especially book texts in libraries and information from the internet, which relate to educational values ​​and morals. The focus of this research is on the values ​​of Moral Education contained in the film